Enlarging Rainfall Area of Tropical Cyclones by Atmospheric Aerosols. Issue 16 (19th August 2018) - Zhao, Chuanfeng; Lin, Yanluan; Wu, Fang; Wang, Yang; Li, Zhanqing; Rosenfeld, Daniel; Wang, Yuan
Abstract: The size of a tropical cyclone (TC), measured by the area of either rainfall or wind, is an important indicator for the potential damage by TC. Modeling studies suggested that aerosols tend to enhance rainfall in the outer rainbands, which enlarges the eyewall radius and expands the extent of rainfall area. However, no observational evidence has yet been reported. Using TC rainfall area and aerosol optical depth (AOD) data, we find that aerosols have a distinguishable footprint in the TC size. Other dynamical factors for TC size, such as relative SST and Coriolis parameter, are also quantified and discussed. We show that, on average, TC rainfall size increases 9–20 km for each 0.1 increase of AOD in the western North Pacific. This finding implies that anthropogenic aerosol pollution can increase not only TC rainfall rate, but also TC rainfall area, resulting in potentially more destructive flooding affecting larger areas. Plain Language Summary: The size of a tropical cyclone (TC), measured by the area of either rainfall or wind, is an important indicator for the potential damage by TC. No observational evidence about the impact of aerosols on the TC size has yet been reported. Using TC rainfall area and aerosol optical depth (AOD) data, we find that aerosols have a distinguishable footprint in the TC size. On average, TC rainfall size increases by 9–20 km for each 0.1 increase in AOD in the western North Pacific. This finding implies that anthropogenic aerosol pollution can increase not only the TC rainfall rate as found in previous studies, but also the TC rainfall area, resulting in potentially more intensive flooding affecting larger areas. It is worthy to note that factors other than the aerosols, such as relative sea surface temperature, could also contribute to the changes of TC rainfall area. Key Points: Aerosols enlarge the tropical cyclone rainfall area in the western North Pacific, which is about 9–20 km for each 0.1 increase in AOD The location of the maximum TC rainfall rate, i.e., TC eyewall, moves farther away from the TC center as AOD increases Total rainfall amount of TC is also found to increase with AOD